Psychological Pathways Linking Public Trust During the Coronavirus Pandemic to Mental and Physical Well-being - Olagoke, Ayokunle A.; Olagoke, Olakanmi O.; Hughes, Ashley M. (Frontiers in Psychology, 2020)
The wellbeing of the public during the 2019 coronavirus (COVID-19) pandemic is deeply rooted in institutional trust in the government's risk communication effort. The objective of this study was to examine the psychological pathway through which public trust in the government is associated with mental and physical wellbeing. We collected cross-sectional data from 501 participants aged ≥18 years. Public trust in the government was assessed as our exposure variable. We screened for psychological distress by combining the Patient Health Questionnaire and the General Anxiety Disorder scale. Physical wellbeing was examined using self-rated health. We further assessed the roles of risk perceptions. One-way analysis of variance (ANOVA), Pearson's correlations, multivariable regressions, and mediation analyses (using the Preachers and Hayes' approach) were conducted. Participants were 55.29% female, 67.86% Caucasian/white with a mean age of 32.44±11.94 years. Public trust in the government regarding COVID-19 was negatively correlated with psychological distress (r = -.20; p<.001) and positively associated with self-rated health (r= .13; p<.001). After adjusting for sociodemographic and socioeconomic factors, public trust remained negatively associated with psychological distress (β= -.19; 95% confidence intervals, [CI] -.30, -.09) and positively associated with self-rated health (β=.26; 95% CI [.16, -.37]). Perceived self-efficacy to practice COVID-19 protective behavior partially mediated the relationship between public trust and psychological distress (13.07%); and self-rated health (28.02%). Perceived self-efficacy to protect self against COVID-19 infection can serve as a psychological pathway through which public trust may be associated with mental and physical health.